Creativity in Early and Established Career: Insights into Multi‐Level Drivers from Nobel Prize Winners. (18th July 2014) - Eubanks, Dawn L.; Palanski, Michael E.; Swart, Juani; Hammond, Michelle M.; Oguntebi, Joy
Abstract : The freedom to try new things plays a vital role for employees engaging in creative endeavors. This freedom can be influenced by one's relationship with her supervisor, relationship with her team, and various work pressures. One of the first steps to reaching creative output is to have a playful attitude toward work where there is encouragement and processes that allow individuals to take risks and try new things. However, we argue that what allows someone to try new things earlier in their career and when they are more established might be different. Noteworthy progress has been made in conceptualizing the multi‐level factors that are important for creativity. In the current study, we identified variables associated with a willingness to try new things, part of the exploration phase of creativity, and divided them by the early and established careers of 59 Nobel Prize winners. Using a historiometric approach, we rated individual and team‐level variables to identify what makes someone try new things either earlier or later in her career. Findings indicate that willingness to try new things is related to autonomy, the relationship with one's mentor, team climate, and team network, but not to personal initiative.